2008
DOI: 10.1093/treephys/28.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Stable annual pattern of water use by Acacia tortilis in Sahelian Africa

Abstract: Water use by mature trees of Acacia tortilis (Forsk.) Hayne ssp. raddiana (Savi) Brenan var. raddiana growing in the northern Sahel was continuously recorded over 4 years. Water use was estimated from xylem sap flow measured by transient heat dissipation. Concurrently, cambial growth, canopy phenology, leaf water potential, climatic conditions and soil water availability (SWA) were monitored. In addition to the variation attributable to interannual variation in rainfall, SWA was increased by irrigation during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…Temperature and D were also higher during November. The observed increase in H v is consistent with previous reports of higher H v associated with higher vapour pressure deficits (Mencuccini and Grace 1995;Do et al 2008). O'Grady et al (1999) found that although W pd and g s were reduced during the dry season, D was higher and adjustments in leaf area played an important role in maintaining a constant rate of water use.…”
Section: Discussionsupporting
confidence: 91%
“…Temperature and D were also higher during November. The observed increase in H v is consistent with previous reports of higher H v associated with higher vapour pressure deficits (Mencuccini and Grace 1995;Do et al 2008). O'Grady et al (1999) found that although W pd and g s were reduced during the dry season, D was higher and adjustments in leaf area played an important role in maintaining a constant rate of water use.…”
Section: Discussionsupporting
confidence: 91%
“…Thus not all of the water that is lost via evapotranspiration is derived from groundwater. Furthermore, the hydraulic architecture of plants adapted to arid and semi-arid environments can limit ET (Eamus et al, 2000;Do et al, 2008). Thus, despite having access to groundwater, it appears that these communities remain water-limited.…”
Section: Discussionmentioning
confidence: 99%
“…internal plant reserves (root, trunk), deep soil layers, or the water table. Indeed, roots which accessed a 30 m deep water table were observed by Do et al (2008) in A. tortilis ssp. raddiana at a north Sahelian site.…”
Section: Overall Analysis 41 Balance Between Deciduous and Evergreenmentioning
confidence: 99%
“…raddiana at a north Sahelian site. These authors cited root depth as the main determining factor of the length of leafing (6.7 months) as well as the intensity of transpiration throughout most of the dry season (Do et al, 1998;Do et al, 2005;Do et al, 2008). Furthermore, some species (e.g.…”
Section: Overall Analysis 41 Balance Between Deciduous and Evergreenmentioning
confidence: 99%